The Correlation between Physical Workload and Musculoskeletal Disorders (MSDs) Complains in Porters at Bersehati Traditional Market Manado - Langi, Intan Allicya Friska; Anderson, Elisa (8ISC Abstract Proceedings, 2022)
Work that depends on physical strength can increase the physical workload. As a result, it leads to Musculoskeletal Disorders (MSDs), which are muscular complaints of the musculoskeletal system. The purpose of this study was to find out the correlation between physical workload and MSDs complaints in the porters at Bersehati Market Manado. This study used a correlational descriptive research design with a cross-sectional approach. There were 87 respondents who were involved, and they were determined by using consecutive technique sampling. The result showed 63.2% of the porters had moderate physical workload, 43.7% of the porters got low MSDs complaints, and there was a significant correlation between the physical workload and the MSDs complaints in the porters at Bersehati Traditional Market Manado (p=0.000 <0.05). The recommendations for the porters are to use work tools to reduce the load weight and to increase the rest time so the physical workload complaints can decrease, and it leads to the reduction of MSDs complaints. Recommendations for the next researchers are to investigate the other factors which can affect the appearance of MSDs complaints, such as weight, working time period, nutritional status, sleep quality, working posture, or mental workload. Keywords : Musculoskeletal Disorders, physical workload, porters, traditional market